EVALUATION OF BEHAVIOR OF CONNECTIONS THROUGH AUTOFLOWING SCREWS IN TREATED RADIATA PINE WOODEN PRESERVATIVES - Galo Cardenas; Diego Ortiz-Ávila; Mario Nuñez-Decap; Alexander Opazo-Vega (Journal of the Chilean Chemical Society, 2021)
Wood is a great material, it has a disadvantage of early deterioration due to external agents. For this reason, it is interesting to create a new wooden preservative. It was studied one based on a natural polymer (chitosan) and nanoparticles (Si and Ti). Tests were carried out to characterize physical (density, moisture content, swelling and absorption) and mechanical properties (flexion, compression and hardness) of wood specimens with and without impregnation, and their joints with two types of self-drilling screws. Simple and lateral extraction test were carried out. Improvements in hardness and perpendicular compression are highlighted obtained, results indicate a stiffening of the fibers. This treatment achieves the material cross section hardening, coating it with components that help to delay the ignition and provide greater duration against external agents. From the extraction of screws, the impregnated wood allowed more rigid unions, with smaller displacements in comparison to the wood without treatment.